Best Proximity Point Results via Measure of Noncompactness and Application. (21st May 2021) - Nashine, Hemant Kumar; Arab, Reza; Patle, Pradip R.; Patel, Deepesh Kumar
Abstract: Best proximity results for cyclic and noncyclic F G -contractive operators in (strictly convex) Banach spaces are obtained via the measure of noncompactness. The work extends some of recent investigations in this direction. The obtained results are applied to investigation of optimum solutions for a system of second order differential equations with two initial conditions followed by an example.